Mechanical behaviour and loading rate dependency of gypsum mixed fine-grained soils under uniaxial loading. Issue 4 (16th August 2021) - Shaikh, Masum; Kyokawa, Hiroyuki; Maqsood, Zain; Ahsan, Md. Kamrul; Koseki, Junichi
Abstract : Gypsum is regarded as one of the environmentally friendly binding materials and widely used to enhance the engineering properties of soft fine-grained soils. However, time-dependent strength and deformation characteristics of fine-grained soils stabilized with gypsum have not yet been thoroughly investigated, and the rational evaluation of these characteristics will assist in the formulation of cost-effective and reliable design approaches. Therefore, in this study, the time-dependent mechanical behaviours of Gypsum Mixed Fine-grained Soils (GMFS) were investigated under unconfined monotonic loading conditions, considering ageing periods ranging from 3 to 90 days and five different loading rates (ranging from 0.0005 to 1.0 %/min). The results revealed that the strength and stiffness of GMFS specimens initially decrease with ageing, and finally become stable after 14 and 28 days of ageing for water/gypsum ratios of 1.30 and 1.60, respectively. Furthermore, the failure strength and stiffness of GMFS increase with the increase of loading rates.